Reverse and negativity: José Manuel Caballero Bonald’s Entreguerras (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The present study focuses on José Manuel Caballero Bonald’s poetic work entitled Entreguerras in which the biographical experiences merge into the linguistic ones. The poetry characterized by elements of antithesis and negativity presents a self-criticism based on oppositions and a poetic word against itself. Moreover, it is an anti-biography in which an ensemble of places in the memory becomes imaginary and textual no-places. It is not the past which builds the self-writing and memory. Rather, it is the poetic duration, which implies the saying-now, that impulses the poet to create and progress along with the past.
Keywords: Caballero Bonald; Entreguerras; poetry; reverse; negativity